2023
DOI: 10.1117/1.nph.10.2.023519
|View full text |Cite
|
Sign up to set email alerts
|

Using functional near-infrared spectroscopy to study the early developing brain: future directions and new challenges

Abstract: . Significance Functional near-infrared spectroscopy (fNIRS) is a frequently used neuroimaging tool to explore the developing brain, particularly in infancy, with studies spanning from birth to toddlerhood (0 to 2 years). We provide an overview of the challenges and opportunities that the developmental fNIRS field faces, after almost 25 years of research. Aim We discuss the most recent advances in fNIRS brain imaging with infants and outlines the trends and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…The here reviewed research suggests fNIRS as an efficient and reliable tool suitable for diverse environments, various populations, and relatively easy to use, which is spreading worldwide (https://gxhorp-federicocurzel.shinyapps.io/musicfNIRSmap/ 2 ; Ayaz et al, 2022;Gervain et al, 2023;Piper et al, 2014). Considering the rising number of studies in this area, and the fact that fNIRS is a relatively recent neuroimaging tool, it is fundamental to acknowledge potential methodological criticisms and follow solid and reproducible experimental procedures.…”
Section: Methodological Considerations and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The here reviewed research suggests fNIRS as an efficient and reliable tool suitable for diverse environments, various populations, and relatively easy to use, which is spreading worldwide (https://gxhorp-federicocurzel.shinyapps.io/musicfNIRSmap/ 2 ; Ayaz et al, 2022;Gervain et al, 2023;Piper et al, 2014). Considering the rising number of studies in this area, and the fact that fNIRS is a relatively recent neuroimaging tool, it is fundamental to acknowledge potential methodological criticisms and follow solid and reproducible experimental procedures.…”
Section: Methodological Considerations and Recommendationsmentioning
confidence: 99%
“…It is also compatible with other neuroimaging or neurostimulation tools, thus enabling multimodal acquisitions (Di Rosa et al, 2019;Qiu et al, 2022;Ru et al, 2022). Numerous studies have shown that fNIRS is an optimal tool for investigating motor and auditory tasks with typical and pathological populations across development (Gervain et al, 2023;Gramigna et al, 2017;Perrey, 2008;Shatzer et al, 2023;. Therefore, fNIRS emerges as particularly suitable for music cognition studies in both laboratory and clinical settings (Chen et al, 2020), including naturalistic and interactive environments (Pinti et al, 2020;Yücel et al, 2017).…”
Section: Basic Principles Of Fnirsmentioning
confidence: 99%
“…Meta-analyses are especially valuable for this type of research questions, as they offer greater sample sizes and statistical power and are thus better able to detect small effects. They have been successfully conducted over behavioral data 31 , 32 , but very few, to date, have been conducted on developmental fNIRS data 33 , 34 , despite the pressing need in the developmental fNIRS community for efforts aimed at addressing issues of replicability 35 . To our knowledge this is the first meta-analysis to address sex differences in neural mechanisms during early human development, measured with fNIRS.…”
Section: Introductionmentioning
confidence: 99%
“…The application of functional near-infrared spectroscopy (fNIRS) to the study of RJA in toddlers and pre-schoolers with ASD can contribute to understanding how peculiarities in the recruitment of brain areas subserving RJA acts are related to atypical social-cognitive development in ASD. In fact, fNIRS is generally considered less demanding for children and relatively robust to motion artifacts compared to scannerbased methods, and its spatial resolution is adequate for the detection of atypicalities in the structure of functional networks at the cortical level (Gervain et al, 2023;Lloyd-Fox et al, 2010;Wilcox & Biondi, 2015). The current study is based on data collected within a randomized controlled trial (RCT) on the effects of an early socialcommunicative intervention on social communication and brain activity in ASD children, the results of which are however not presented here (see Methods section for clarifications).…”
Section: Introductionmentioning
confidence: 99%